Jimi Hendrix and the Cultural Politics of Popular Music - Lefkovitz, Aaron (Springer International Publishing, 2018)
This book, on Jimi Hendrix's life, times, visual-cultural prominence, and popular music, with a particular emphasis on Hendrix's relationships to the cultural politics of race, gender, sexuality, ethnicity, class, and nation. Hendrix, an itinerant "Gypsy" and "Voodoo child" whose racialized "freak" visual image continues to internationally circulate, exploited the exoticism of his race, gender, and sexuality and Gypsy and Voodoo transnational political cultures and religion. Aaron E. Lefkovitz argues that Hendrix can be located in a legacy of black-transnational popular musicians, from Chuck Berry to the hip hop duo Outkast, confirming while subverting established white supremacist and hetero-normative codes and conventions. Focusing on Hendrix's transnational biography and centrality to US and international visual cultural and popular music histories, this book links Hendrix to traditions of blackface minstrelsy, international freak show spectacles, black popular music's global circulation, and visual-cultural racial, gender, and sexual stereotypes, while noting Hendrix's place in 1960s countercultural, US-exceptionalist, cultural Cold War, and rock histories.